Exploratory study on maturation and competition level in young karate practitioners (Revista de Artes Marciales Asiáticas, 2019)
Paring children improve the chance for success and reduce injury in sport. Despite the maturity differences between children, chronological age remains the main criterion to equalize competition levels, but with limited efficiency. However, in Karate, weight is also considered. We went to investigate the association between chronological age and maturational indicators and find simple models to put on reflection new ways to assess the maturity. Data were collected in 54 young Karate practitioners (age: 12.67 ± 2.49 years, experience: 4.99 ± 2.44 years, height: 150.45 ± 15.25 cm, weight: 43.09 ± 14, 17 kg, 20 girls). Age correlated significantly with self-observation of sexual maturation (rho = 0.838; p < 0.01), and it was possible to find simple regression models that have a moderate explanation in maturation, using only simple measurable variables such as the height, weight and arm circumference. These results should lead the competent entities to reflect on the way of pairing of the athletes in the competitions, in a fair way in terms of maturation.